Three contemporary objections to theistic ethics - Choo, Frederick Wen Yeong (Nanyang Technological University, 2021)
In this thesis, I consider three contemporary objections against theistic ethical theories like Divine Command Theory (DCT). I argue that these objections ultimately fail. The first objection is the prior obligations objection. For DCT to be plausible, it seems that there must be a moral obligation to obey God’s commands. But to avoid circularity, the moral obligation to obey God’s commands must be grounded independent of God’s commands. Hence, there must be a prior moral obligation to obey God’s commands. However, since this prior obligation is grounded independent of God’s commands, DCT would fail to ground all moral obligations in God’s commands. The second objection is the terrible commands objection. Theistic ethical theories imply that if God commanded, desired, or willed, a terrible act, then the terrible act would be right. This yields the implausible result that terrible acts could possibly be morally right. The third objection is the promulgation objection. The objection says that theistic ethical theories must include an appropriate epistemic requirement; but such a requirement would exempt groups of people, such as reasonable non-believers and psychopaths, from morality because these groups of people would fail to satisfy the epistemic requirement. So, DCT implausibly exempts these groups of people do not have moral obligations.